Evaluation of Technological and Phenolic Maturation of Grapes and Wine Aromatic Profile under Subtropical Conditions - Bonin, B.; Biasi, L. A.; Filho, J. L. M.; Brighenti, A. F.; Soldi, C.; Franciscon, V.; Cosmo, A. C. (South African Journal of Enology and Viticulture, 2025)
The purpose of this study was to evaluate the technological and phenolic maturation of ‘Cabernet Sauvignon’, ‘Merlot’, ‘Pinot Noir’, ‘Fiano’ and ‘Viognier’ grapes, as well as their wines sensory and volatile profiles, under subtropical conditions in southern Brazil. The experiment was conducted during the 2020/2021 and 2021/2022 growing seasons. The must physicochemical parameters analysed were pH, total soluble solids, total titratable acidity, total polyphenols, total anthocyanins, and total tannins. Volatile compounds in the wines were determined using gas chromatography (HS-SPME-GC/MS). Sensory analysis was performed using visual, olfactory and taste parameters, with quantitative assessments based on rating scales. The total soluble solids ranged from 18.1°Brix (‘Viognier’) to 19.8°Brix (‘Pinot Noir’), while titratable acidity varied from 7.40 g/L (‘Merlot’) to 9.48 g/L (‘Pinot Noir’). The grapes from all cultivars exhibited suitable parameters for technological and phenolic maturation, with distinct characteristics such as adequate pH, total soluble solids, and slightly elevated total titratable acidity. Sensory analysis of the red wines revealed profiles characterised by red fruit, earthy/animal and floral notes, with key volatile compounds such as isoamyl alcohol, phenylethyl alcohol, diethyl succinate and isoamyl acetate. The sensory profile of the white wines was related to citrus, sweet fruit and floral aromas, attributed to the presence of citronellol, β-damascenone, ethyl-2-phenylacetate and ethyl octanoate. The results of this study provide valuable insights into the characteristics of wines produced in this emerging wine region of southern Brazil, contributing to a better understanding of the region’s viticultural potential.